Community Response to the Existence of Mural Artwork in Gampong Peunayong, Banda Aceh City - Aulia, Nindi; Taruan, Hatmi Negria; Husni, Teuku Muhammad (Institut Seni Indonesia Padang Panjang, 2024)
Mural art is a work of fine art that is depicted on a large, flat medium, such as the wall or ceiling of a room. Murals first appeared as a means of aspiration during the Indonesian war for independence. At that time, the street walls were covered with various kinds of critical and satirical murals. This research activity was carried out in Gampong Peunayong, Banda Aceh City. This research aims to find out how traders and the local community react and respond to the existence of murals on the walls of Gampong Peunayong buildings. In terms of examining research objects and subjects, researchers use qualitative research methods, which discuss descriptively the entire data obtained during the research. As a supporting tool, researchers used Clive Bell's Form Theory to examine the shapes in the murals in Gampong Peunayong briefly. The research method used is qualitative research. This research aims to find out how the local community that lives around the murals exists and examine information about the murals depicted on the walls of Gampong Peunayoung. Based on the results of research in the form of explanations and responses from the community regarding the existence of murals in Gampong Peunayong, some people accept and are happy with the presence of murals in their environment, especially traders at the Peunayong market. However, some others did not like the visual mural that was presented. The impact of murals on the economic growth of traders at Peunayong Market is also not really felt; whether or not there are murals, traders still have customers.